CHORIONIC VILLUS SAMPLING: A SAFE TOOL FOR PRENATAL DIAGNOSIS OF GENETIC DISORDERS: Chorionic Villus Sampling - Sultana, Nadra; Hayat, Zartaj; Nasim, Iffat (Pakistan Armed Forces Medical Journal, 2009)
Objectives: To determine the safety and efficacy of chorionic villus sampling (CVS) for early prenatal diagnosis of genetic disorders.Study Design: Descriptive study.Place and Duration of Study: Department of Obstetrics and Gynecology, Foundation University Medical College, Rawalpindi, from December 2002 to April 2006.Patients and Methods: Subjects who had high risk factors like personal or family history of genetic disorders were referred to us for CVS after 10 gestational weeks. Under local anaesthesia and ultrasound guidance (USG) guidance a special chorion biopsy double needle (outer guide and inner aspiration needle) was introduced through anterior abdominal wall into placenta to obtain specimen from chorionic villi. Women were observed for 1-2 hours to notice any immediate complications like uterine cramps and vaginal bleeding. Follow up was done till end of pregnancy to know the outcome. Specimen obtained was sent to laboratory for DNA analysis to diagnose β-thalassaemia in 234 patients and for karyotyping to diagnose Down’s syndrome in 17 patients.Results: Of 252 CVS performed, sample was successfully obtained in 99.6% of cases and only one procedure failed. Most common indication was β-thalassaemia (93.0%). The immediate complications were uterine cramps in 41 (16.3%), vaginal bleeding in one (0.8%) and amniotic cavity puncture in six (2.4%) subjects. Noteworthy was the fact that miscarriage rate was quite low (2.4%). At follow up no evidence of incorrect sampling was reported .Of 234 specimens obtained for DNA analysis, 23.5% were homozygous for β-thalassaemia, to whom termination of pregnancy (TOP) was offered to prevent birth of an abnormal baby.Conclusion: CVS is a safe and effective method for early prenatal diagnosis of genetic disorders. Its use can help in early detection and prevention of birth of babies with lethal genetic disorders.